Waterfront Management in the Areas Around Lake Sidihoni to Support Sustainable Economic and Tourism Development - Imelda Florence Situmorang; Zulkifli Nasution; Rujiman (Formosa Journal of Applied Sciences, 2023)
This qualitative study was undertaken to gather information about the present status of the Lake Sidihoni region by watching government and community members and conducting interviews. The data and information gathered utilizing the triangulation approach were checked and rechecked based on the information received. From the findings of identifying current circumstances, existing information/data is mapped using the SWOT approach to assess the organization's strengths, weaknesses, opportunities, and threats. The overall results of these stages are the concept of structuring Lake Sidihoni for sustainable economic and tourism development with a waterfront approach, namely by increasing the value and function of the waterfront that supports recreational activities by utilizing the physical conditions of Lake Sidihoni, namely: 1) The management is not well organized/managed where available facilities (amenities) where the facilities and infrastructure to support recreational activities; 2) The management is not well organized/managed where available facilities (amenities) where the facilities 2) Limited human resources (HR) and ineffective institutions, as shown by the absence of HR and social institutions in the tourist industry, as well as the private sector's lack of direct investment interest in the tourism sector. 3) Based on the regional spatial planning of Samosir Regency, it has been designated as a protected area, therefore its configuration is restricted. 4) The institutional factor is still a barrier since there is no tourism institution in the area, therefore visitors do not feel secure and protected while visiting the area.